CFD analysis of thermal comfort in hospital operation room with different air distribution design and operative temperature / Hazran Husain, Muhamad Zharif Mohd Samidi and Mohd Suhairil Meon - Husain, Hazran; Mohd Samidi, Muhamad Zharif; Meon, Mohd Suhairil (Smart Manufacturing Research Institute (SMRI), 2021)
The operation room is one of the most critical regions in hospital that require extra attention in air ventilation and prevention of dangerous pollutants contamination. A good level of ventilation will help to raise the productivity of workers in terms of performance and ensuring a safe surgery operation. It is obvious that today's operation rooms are completely equipped with mechanical ventilation systems. However, despite the fact that they meet the acceptable comfort standards, surgical workers have complained about thermal discomfort during operation which gives negative impact on their performance. Thermal comfort can be achieved by controlling the temperature, relative humidity and air movement. In this study, the operation room models are simulated to analyze the comfort conditions of surgical workers under 3 different air velocities at 0.2 ms-1, 0.25 ms-1 and 0.35 ms-1 and under 5 different temperatures between 16℃ to 20℃. Additionally, there are two 3D models created with different position of exhaust vent. The thermal comfort of surgical workers is measured using Predicted Mean Vote (PMV) and Predicted Percentage Dissatisfied (PPD) approaches using CBE Thermal Comfort Tool. The PMV and PPD results show that most surgical workers were outside the acceptable range value of -0.5 to +0.5 stated in ASHRAE Standard 55-2020. According to thermal scale index, most of the surgical workers were in a cool and slightly cool state despite the fact that the computational analysis shown an acceptable simulation validated with previous research studies. Finally, it has been discovered that clothing insulation, metabolic rate, mechanical equipment and air distribution design play a significant influence in providing comfort to the surgical workers.